Contact tracing for chronic hepatitis B in primary care? A 'snapshot' audit in Grampian, Northeast Scotland. Issue 3 (August 2018) - Phillips, Bethan; Corrigan, Helen; Okpo, Emmanuel
Introduction: Contact tracing for chronic hepatitis B infection is an important activity for preventing the spread of hepatitis B infection. In the UK, the 'Green Book' recommends that all sexual and household contacts of individuals with chronic hepatitis B should be tested and vaccinated if required. This audit aimed to evaluate contact tracing in primary care. Barriers to effective follow-up of contacts of patients with chronic hepatitis B were explored and recommendations made. Methods and results: Mixed method, including a survey of general practitioners and review of hepatitis B surveillance data from 1 June 2015 to 31 December 2015 held by NHS Grampian Health Protection Team. The audit was carried out in August 2016. Contact tracing was mainly by patient referral. Only 20% (4/20) of identified close contacts were tested. No contact eligible for vaccination was vaccinated, and 57% (8/14) of general practitioners who completed the audit questionnaire suggested that general practitioners do not have a role in contact tracing. Barriers identified were: lack of time, lack of resources and contacts being registered with a different practice. Conclusions: This audit suggests that contact tracing for chronic hepatitis B in primary care is largely incomplete. Moving contact tracing from general practice to health protection teams in Boards may be a pragmatic way of improving follow-up activities.